Analysis of the Role of Social Services in Improving Community Welfare in Islamic Economic Studies (Case Study at the Office of Social Protection and Social Security in Mandailing Natal Regency) - Sri Sudiarti; Rina Sari (Penerbit Jurnal Indonesia, 2022)
The Social Service is the implementing element of government affairs in the social sector. The Social Service is led by a Head of Service who is under and responsible to the Regent through the Regional Secretary. The Social Service has the task of assisting in the social sector, including Social Rehabilitation, Social Empowerment, Social Security Protection and Handling the Poor. Along with the many natural and non-natural disasters that occurred in Mandailing Natal, the role of the Social Service is very much needed in order to improve the welfare of the people affected by natural and non-natural disasters. This study aims to determine the role of the Department of Social Affairs in the field of Social Security Protection in improving the welfare of people affected by disasters and non-natural disasters in Mandailing Natal Regency. This study uses qualitative methods and the data used are primary and secondary data. The subject of the research was carried out at the Social Service of Mandailing Natal Regency.